2021
DOI: 10.3390/app11146573
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Properties of Seismicity and Variations of Shear-Wave Splitting Parameters in the Western Gulf of Corinth (Greece)

Abstract: The Western Gulf of Corinth (WGoC) exhibits significant seismicity patterns, combining intense microseismic background activity with both seismic swarms and short-lived aftershock sequences. Herein, we present a catalogue of ~9000 events, derived by manual analysis and double-difference relocation, for the seismicity of the WGoC during 2013–2014. The high spatial resolution of the hypocentral distribution permitted the delineation of the activated structures and their relation to major mapped faults on the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…Both the abovementioned hydraulic diffusivity and the migration rate are comparable with the respective values previously measured in fluid-associated earthquake triggering at the Western Corinth Gulf (e.g., [9,10,12,94,95]). Seismic swarms are commonly observed in areas related to volcanic activity, involving magmatic or hydrothermal fluids (e.g., the 2008-2009 swarm at Yellowstone Lake [96] or the 2008 swarm at Vogtland/NW Bohemia [97]), or induced by water injection in geothermal fields (e.g., the 1993 swarm in Soultz-sous-Foret, France [98]).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Both the abovementioned hydraulic diffusivity and the migration rate are comparable with the respective values previously measured in fluid-associated earthquake triggering at the Western Corinth Gulf (e.g., [9,10,12,94,95]). Seismic swarms are commonly observed in areas related to volcanic activity, involving magmatic or hydrothermal fluids (e.g., the 2008-2009 swarm at Yellowstone Lake [96] or the 2008 swarm at Vogtland/NW Bohemia [97]), or induced by water injection in geothermal fields (e.g., the 1993 swarm in Soultz-sous-Foret, France [98]).…”
Section: Discussionsupporting
confidence: 86%
“…Thiva (Central Greece) is located at the transition zone between two major WNW-ESEand NW-SE-striking rifts: the Corinth Gulf in the south and the Euboekos Gulf in the east (Figure 1). The Gulf of Corinth is an area characterized by high seismicity [6,7] expressed through the frequent occurrence of seismic swarms [8][9][10][11][12]. [13] are shown, along with the locations of seismological stations of the Hellenic Unified Seismic Network (HUSN; red triangles) and GNSS stations (inverse yellow triangles).…”
Section: Introductionmentioning
confidence: 99%
“…The sequences in the Corinth Gulf in particular are characterized by the highest background rate among the three areas (Table 5), meaning that a significant portion of clustered seismicity is not caused by the triggering of a main shock coseismic slip, but by the contribution of different triggering mechanisms. Many studies have focused on this area, suggesting pore-pressure changes due to fluid migration and aseismic creep as possible triggering mechanisms for the clustered seismicity [57,71]. In the North Aegean Sea, the swarm activity coexists with aftershock sequences, implying that for forecasting purposes, a finer regionalization might be more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is a slight decrease in the occurrence of earthquakes (λ 1 = 1.23 events/day) in the second part of the catalog, starting from 02/2016 with transitions to state 1 (red color, Figure 3a) until almost the end of the catalog in 12/2019. This is probably related to the lack of seismic sequences during the last part of the study period compared to the previous intense seismic activity especially during the period 2013-2014 in the western subarea of the CG [57]. The rate threshold is set equal to λ thr = λ 2 , which we consider as the background rate during the study period.…”
Section: Triggered and Background Seismicity Separationmentioning
confidence: 99%
“…The use of the freely available CRL data highlighted that most seismicity is clustered, with the frequent occurrence of swarms, as the 2001 Agios Ioannis [Pacchiani and Lyon-Caen, 2010], the 2013 Helike [Kapetanidis et al, 2015[Kapetanidis et al, , 2021Kaviris et al, 2017] and the 2015 Malamata [De Barros et al, 2020] ones. Geodetic studies, from permanent and campaign GNSS network measurements and InSAR, identified the deformation sources of the Aigion [1995] and Efpalio [2010] earthquakes, as well as slow aseismic shallow slip [Elias and Briole, 2018].…”
Section: The Corinth Rift Laboratory (Crl)mentioning
confidence: 99%